Yolov5 Based Fault Detection Approach in Railway Components - Yilmazer, Merve; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2023)
For safe transportation on the railway, the faults occurring in its components must be detected and repaired. Recently, fault detection methods have been developed on railway visual data using methods such as image processing, machine learning and deep learning. Especially since deep learning-based algorithms have a self-learning structure, the data used in model training and testing significantly affect the performance of the model. In the proposed method within the scope of this study, railway visual data were obtained using autonomous drone. YOLOv5 deep neural network is trained to detect faults that may occur in various components such as rail, fastener, sleeper and ballast in the railway. In order to increase the efficiency of the model, images obtained under different lighting conditions were included in the data set. In addition, by using the OpenCV library, the video stabilization process and the vibrations that occur during data acquisition in the video are eliminated. Thus, with the proposed method, it has been shown that the errors due to many components in the railway can be detected with a mAP rate of 94.5%. © 2023 IEEE.
27th International Conference on Information Technology, IT 2023 -- 15 February 2023 through 18 February 2023 -- Zabljak -- 187585
Keywords: autonomous drone; deep learning; railway fault detection